2016
DOI: 10.1186/s40854-016-0033-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of private sector credit in Uganda: the role of mobile money

Abstract: Background: Mobile money services have been associated with unprecedented access to financial services, notably to under-banked and unbanked populations. Thus, mobile money opens a channel through which to examine the supply of private sector credit in Uganda. This study investigates how mobile money services influence private sector credit growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…In a similar vein, a positive relation between MM balances and private sector credit was established in Uganda (Mawejje & Lakuma, 2017). Adding weight to these findings, Nampewo et al (2016) found that MM balances led to private sector credit growth in the long run, suggesting the expansion of financial depth.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar vein, a positive relation between MM balances and private sector credit was established in Uganda (Mawejje & Lakuma, 2017). Adding weight to these findings, Nampewo et al (2016) found that MM balances led to private sector credit growth in the long run, suggesting the expansion of financial depth.…”
Section: Resultsmentioning
confidence: 99%
“…While previous studies like Aker and Mbiti (2010); Wesolowski, Eagle, Noor, Snow, and Buckee (2012); Muto and Yamano (2009); Nampewo et al (2016); Donovan (2012); Lochan et al (2010); Morawczynski (2009); (Jack and Suri, 2014) suggest that use of mobile money can transform and ease access to financial services, especially in developing countries, they fail to integrate the trust element in their analyses. Besides, Choi and Kim (2012); Schaupp and Carter (2005); Xenakis and Macintosh (2005) have used trust effect on acceptance of information systems.…”
Section: Introductionmentioning
confidence: 92%
“…Mobile money has helped bring 194,000 Kenyans out of poverty [1]. In 2008, Vodacom launched M-Pesa while Zantel launched Z-Pesa in Tanzania [19]. MTN mobile money in Uganda was launched in 2009 with at least 1000 users.…”
Section: Mobile Money Adoption In East Africamentioning
confidence: 99%
“…MTN mobile money in Uganda was launched in 2009 with at least 1000 users. Since its launch, several other players like Airtel money, M-cash, Ezee-money, M-Sente and Orange money have also joined the Ugandan market [19]. Micropay is the latest entrant to the Ugandan mobile money market, bringing the number of service providers to seven [24].…”
Section: Mobile Money Adoption In East Africamentioning
confidence: 99%